Misogynistic Values in Indonesian Horror Films (Critical Discourse Analysis of Sarah Mills on the Film Rumah Dara) - Rana Akbar Fitriawan; Haris Annisari Indah NR; Wa Ode Suci Rahmayani (Green Publisher Indonesia, 2025)
This study aims to analyze the representation of women in the Indonesian horror film